(untitled) (The International Research Journal of Management Science, 2024)
Purpose: The purpose of the paper is to identify the moderating role of socially constructed gender-based norms in the relationship between institutional support and entrepreneurial survivability based on women entrepreneurs’ perceptions. Method/ Design: The study follows a causal research design. The population comprises all women entrepreneurs from all over Nepal with purposively selected 353 samples from conveniently selected four provinces. The moderation effect was tested with the application of Structural Equation Modeling based on the institution theory using SPSS with AMOS. Exploratory Factor Analysis, Confirmatory Factor Analysis, and moderation test were conducted to find the results in the three-step processes. Findings: Findings showed that the moderating effect of gender-based norms weakened the relationship between institutional support and survivability. Implications: A policy implication of the study requires consideration of gender norms while providing support to women entrepreneurs. Regarding the practical implications of the policies, women entrepreneurs should be made more knowledgeable about the socially constructed problems in their entrepreneurial journey. Originality/Limitation of the Study: This study contributes to the growing literature and body of knowledge in the field of entrepreneurship especially in the context of Nepal. Conclusions are based on only the perception of women entrepreneurs. The study conclusions are unique and might not apply in the context of a developed economy. A comprehensive and detailed understanding can be obtained from the analysis of different perspectives on women’s entrepreneurial survivability.